Characterization and deorphanization of RYamide signaling in Aedes aegypti: A potential regulator of hindgut-associated physiology - Jinghan Tan; Thomas Luong; Jean-Paul V. Paluzzi (PLoS ONE, 2026)
Neuropeptide Y-related signaling, consisting of various neuropeptides and their receptors including, for example, the mammalian neuropeptide Y (NPY), pancreatic polypeptide (PP), and peptide YY (PYY) families, along with neuropeptide Y-like peptides in insects, is evolutionarily conserved across vertebrates and invertebrate organisms. Vertebrate NPY is known as an important regulator of energy homeostasis and feeding behaviour, while studies on one NPY-associated signaling system in arthropods, known as RYamide, have mainly focused on functions regulating feeding-related behaviours. The current study aimed to begin exploring an additional functional role of RYamide signaling related to excretory physiology in Aedes aegypti given that a candidate RYamide receptor, RYaR2, is enriched in the hindgut of adult mosquitoes based on publicly available RNA-seq databases. Herein, we report that the RYamide transcript is expressed in all post-embryonic stages with greatest abundance in adult male mosquitoes. Specifically, the central nervous system and the ventral nerve cord were demonstrated as the major sources of RYamide, as supported by RT-qPCR and intense RYamide immunoreactivity observed in the protocerebral posterior dorsomedial neurons and protocerebral anterolateral neurons in the mushroom body region, along with an intensively stained pair of neurons in the terminal abdominal ganglion (TAG). The pair of immunoreactive neurons in the TAG contain elaborate processes extending onto the hindgut, with a branch extending posteriorly over the rectum where fine processes are in close proximity to the rectal papillae (pads) while an anterior branch extends over the ileum terminating at the midgut-hindgut junction forming a fine circular plexus over the pyloric valve. Importantly, two orphan GPCRs, previously referred to as NPYLRs, were functionally deorphanized as bona fide RYamide receptors. Their responses to diverse peptidergic ligands were assessed, revealing that RYamides elicited the strongest receptor activation, with half maximal effective concentrations in the pico- to nanomolar range. Notably, our phylogenetic analysis revealed that while only a single RYaR is commonly found across most arthropods, culicine mosquito species including A. aegypti possess two RYaRs. The characterization of RYamide signaling with respect to excretory physiology involving the hindgut, particularly in species having two receptor isoforms such as culicine mosquitos, may provide valuable insights for development of novel, species-specific pest control strategies.